When solvent becomes reactant: a study of 6‐aminothiocytosine derivatives. Issue 10 (29th September 2020) - Grześkiewicz, Anita M.; Ostrowska, Agata; Borzylo, Dmytro; Kubicki, Maciej
Abstract : The dissolution of 6‐aminothiocytosine in common solvents (such as methanol, dimethyl sulfoxide and dichloromethane) under alkaline conditions is shown to afford four new compounds with a 6‐aminothiocytosine skeleton. The crystal architectures of these compounds are found to be strongly influenced by extensive hydrogen‐bond networks, although some individual features are also observed. Abstract : The dissolution of 6‐aminothiocytosine in common solvents (such as methanol, dimethyl sulfoxide and dichloromethane) under alkaline conditions is shown to afford new compounds with a 6‐aminothiocytosine skeleton: 2, 2′‐disulfanediylbis(pyrimidine‐4, 6‐diamine) (1 ), C8 H10 N8 S2, 2, 2′‐[methanediylbis(sulfanediyl)]bis(pyrimidine‐4, 6‐diamine) (2 ), C9 H12 N8 S2, 2‐[(methoxymethyl)sulfanyl]pyrimidine‐4, 6‐diamine (3 ), C6 H10 N4 OS, and poly[(μ‐4, 6‐diaminopyrimidine‐2‐sulfinato)potassium(I)] (4 ), [K(C4 H5 N4 O2 S)] n . The crystal architectures of these compounds are found to be strongly influenced by extensive hydrogen‐bond networks, although some individual features are also observed. Specifically, 1 is characterized by very short C—H…N hydrogen bonds, 2 features apparently weak and long C—H…π, C—H…S and π–π contacts as the greatest contributors to stabilization energy, while 3 contains ribbons of molecules formed by centrosymmetric dimers of two types, and 4 is characterized by layers with principal structural units comprising distorted six‐molecule rings. The intermolecular interactions in 1 –4 are characterized in terms of their geometry, topology and energy, and the corresponding results are confirmed and visualized using Hirshfeld surface analysis.